2012
DOI: 10.1016/j.expneurol.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A novel zebrafish model of hyperthermia-induced seizures reveals a role for TRPV4 channels and NMDA-type glutamate receptors

Abstract: Febrile seizures are the most common seizure type in children under the age of five, but mechanisms underlying seizure generation in vivo remain unclear. Animal models to address this issue primarily focus on immature rodents heated indirectly using a controlled water bath or air blower. Here we describe an in vivo model of hyperthermia-induced seizures in larval zebrafish aged 3 to 7 days post-fertilization (dpf). Bath controlled changes in temperature are rapid and reversible in this model. Acute electrograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(59 citation statements)
references
References 45 publications
2
53
1
Order By: Relevance
“…To our knowledge, neither TRPV2 nor TRPV3 have been reported to have any involvement in epilepsy, while only a single study to date has suggested the involvement of TRPV4 in epilepsy [135]. Here, TRPV4 blockade was proposed to reduce febrile seizures in larval zebrafish [136], and so, again, the ability of CBD to activate TRPV4 would be in direct contrast to its clear anticonvulsant effects.…”
Section: Cbd Ion Channel Targets In Epilepsymentioning
confidence: 86%
“…To our knowledge, neither TRPV2 nor TRPV3 have been reported to have any involvement in epilepsy, while only a single study to date has suggested the involvement of TRPV4 in epilepsy [135]. Here, TRPV4 blockade was proposed to reduce febrile seizures in larval zebrafish [136], and so, again, the ability of CBD to activate TRPV4 would be in direct contrast to its clear anticonvulsant effects.…”
Section: Cbd Ion Channel Targets In Epilepsymentioning
confidence: 86%
“…Recently, it has been reported that hyperthermiainduced seizures recorded in the larval zebrafish forebrain are blocked by the application of TRPV4 and NMDAR antagonists, revealing a possible role for TRPV4 in seizure [42]. Concerning the characteristics of multipolar activation, TRPV4-induced regulation of ion channels or receptors may play an important role in pathological conditions, such as seizure and cerebral ischemia [20,42], thus making TRPV4 a promising target for the development of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the characteristics of multipolar activation, TRPV4-induced regulation of ion channels or receptors may play an important role in pathological conditions, such as seizure and cerebral ischemia [20,42], thus making TRPV4 a promising target for the development of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…These include modulation of the function of specific ions channels. For example, the transient-receptor-potential vanilloid (TRPV) 1 and 4 channels are regulated by brain temperature in the physiological and fever ranges, and have been implicated in febrile seizures in animal models [49] where elevated brain temperature leads to augmented neuronal firing, facilitating seizures. Similarly, HCN channels [22,50] and Cav1.2 calcium channels [51] seem to contribute to the hyperexcitability that results in febrile seizures.…”
Section: How Are Fs Generated?mentioning
confidence: 99%